The impacts of surgical intensive care unit admission source on morbidity and mortality outcomes: The results from the THAI-SICU study - Thammasak Thawitsri (2018)
© 2016, Medical Association of Thailand. All rights reserved. Objective: The present study aims to examine the association between admission source and outcomes in surgical ICU (SICU) patients. Material and Method: The data in the present report were retrieved from the THAI-SICU database which was designed as a multi-center prospective observational study. The data were collected at 9 university-based surgical ICUs over 22 months from April 2011 to January 2013. Results: The sources of SICU admissions were categorized into operating room (OR) group with 3,238 admissions (69.6%), emergency room (ER) group with 499 admissions (10.7%), ward group with 825 admissions (17.7%), and other ICUs group with 90 admissions (1.9%). In view of transfer from other hospitals, the transfer group included 938 patients (20.2%) while the non-transfer group included 3,714 patients (79.8%). Patients admitted from other ICUs were nearly three-times more likely to die in SICU (adjusted odds ratio (OR) 2.89; 95% confidence interval (CI) 1.52-5.51, p = 0.001) than those who came from operating room. However, the ward group still had a high risk to dying (OR 2.49; 95% CI 1.88-3.30, p<0.001). In view of outcomes for inter-hospital transfer patients, the transfer group was at greater risk of dying in SICU and had greater risk of 28-day mortality than the non-transfer group. Conclusion: Surgical, critically ill patients, who transferred from other ICUs to SICU, have the highest risk of ICU morbidity and mortality. In addition, ward patients and transfer patients also have high risk of unfavorable outcomes.